A Case of Simultaneous Unilateral Anterior and Posterior Stafne Bone Defects. (29th October 2015) - Ozaki, Hisashi; Ishikawa, Shigeo; Kitabatake, Kenichirou; Yusa, Kazuyuki; Tachibana, Hirohiko; Iino, Mitsuyoshi
Abstract : Stafne bone defects (SBDs) are asymptomatic mandibular lingual bone depressions mainly caused by soft tissue inclusions. The most common form of SBDs is posterior; the anterior variant of SBD is relatively uncommon. Although posterior SBD is easily diagnosed by the unique location on radiography, anterior SBD is sometimes misdiagnosed and confused with other pathological entities owing to the location. We report herein a case of simultaneous unilateral anterior and posterior SBDs. In the present case, definitive diagnosis for the anterior mandibular cavity was unclear, as in reported cases. Surgical exploration was thus performed for the lesion in the anterior mandibular cavity. Pathologic examination of the removed tissue showed salivary gland with chronic inflammation. Postoperatively, no functional disturbance has been observed. Management of the posterior SBD was conservative, with radiographic follow-up. To the best of our knowledge, this represents the first report of simultaneous unilateral anterior and posterior SBDs.